Clinical outcome and prognostic factors of patients with non-traumatic angiography-negative subarachnoid hemorrhage - Geng, Yibo; Jia, Jianwen; Liu, Xiaoli; Li, Tong; Liu, He; Sun, Yongquan; Wang, Yang (Frontiers in Neurology, 2023)
Purpose The cause of spontaneous subarachnoid hemorrhage (SAH) is unknown in 10% of cases. The aim of this study was to demonstrate the characteristics of patients with angiography-negative subarachnoid hemorrhage (anSAH) and to analyze factors influencing the clinical outcome in patients suffering from anSAH. Methods A retrospective cohort of 75 patients with anSAH [26 perimesencephalic (pmSAH) and 49 non-perimesencephalic SAH (npmSAH)] admitted between January 2016 and June 2022 was included. We analyzed demographic, clinical data and 6-month functional outcomes. Enter regression analysis was performed to identify factors associated with outcomes. Results Unfavorable outcome was achieved in 10 of 75 patients (13.3%). Unfavorable outcome was associated with senior adults (p = 0.008), Hijdra cistern score (HCS) elevation (p = 0.015), long-time lumbar cistern continuous drainage (LCFD; p = 0.029) and hydrocephalus (p = 0.046). The only significant risk factor for unfavorable outcome after npmSAH was the HCS (OR 1.213 (95%CI 1.007–1.462), p = 0.042). Conclusion Our study provides valuable information on both SAH patterns and functional outcome in patients suffering from anSAH and should be taken into consideration during management of these patients.